Legal Impact From Lambe Turah Account Relating To Article Of Insult And Prohibited Conduct - Anjani, Risa Gia; Ramadhani, Dwi Aryanti; Dirkareshza, Rianda (Veteran Law Review, 2020)
Instagram is an information dissemination platform that is very attractive to Indonesians. The popularity of the Lambe Turah gossip account on social media Instagram is not necessarily free from the applicable legal rules, that all social media activities related to insulting and spreading the privacy of others is a violation that refers to the Criminal Code and the Law Information and Electronic Transactions. The research method in this scientific work is a normative-juridical study, using the statute approach and analyzed qualitatively. Lambe Turah's "Hengpon Jadul" content is unlawful because it has spread the personal information of others which often results in hate speech comments from followers, which can lead to defamation. The anonymity used by the Lambe Turah admin can be revealed with the help of the Cyber and Code National Agency or in collaboration with related social media companies. So that something similar does not happen again, law enforcement should be able to supervise entertainment accounts on social media.Keywords:Â Lambe Turah, Spread of Privacy, Anonymity.